If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(3-(5+2x)-2x)=-16+2(1-8x)
We move all terms to the left:
7(3-(5+2x)-2x)-(-16+2(1-8x))=0
We add all the numbers together, and all the variables
7(3-(2x+5)-2x)-(-16+2(-8x+1))=0
We calculate terms in parentheses: -(-16+2(-8x+1)), so:We get rid of parentheses
-16+2(-8x+1)
determiningTheFunctionDomain 2(-8x+1)-16
We multiply parentheses
-16x+2-16
We add all the numbers together, and all the variables
-16x-14
Back to the equation:
-(-16x-14)
7(3-(2x+5)-2x)+16x+14=0
We add all the numbers together, and all the variables
16x+7(3-(2x+5)-2x)+14=0
We move all terms containing x to the left, all other terms to the right
16x+7(3-(2x+5)-2x)=-14
| 6(3x-4)=46 | | ((2x^2)/x+1)+1=(2/(x+1)) | | 7(x+4)+3(x+4)=5x-5 | | -2t^2+15t-50=0 | | y-10.24=5.23 | | |2x-6|=22 | | x/3-3/4=(2x+9/12) | | 5x=4x+6+16/x | | x+7=2x+5−4x | | 3/z=15/7 | | 2x^2/x+1+1=2/x+1 | | 8(z-2)=9z-18 | | 2(z+4)=4z+2 | | 26−4s=9s26−4s=9s | | Y=40000-0.2x | | 6a−3(3a−3)=30 | | 6x2-8=0 | | 1.208^14t=3 | | 2.7+9/2y=4.3 | | 7(y-8)=2y-1 | | 2/3c+8=14 | | 5w+9=0 | | 14v+11v+-19v–20v–11v–-5=-20 | | 2(x+5)=6x-6 | | 3y=32+y | | 30+8b=2+5(5b-8 | | -4p-5(2-3p)=6(p-4)-26 | | -3(x-6)=18 | | 3(m+4)=5m | | 25-4x-18-3x=42 | | 5k+12=7k-6 | | (x-8)/4=(x-3)/3 |